A Mathematical Framework for Optimizing the Routing Model for Quality of Service using Decision Based Path Formation in Cluster Based Wireless Sensor Network - NAGESH.R, Dr SARIKA RAGA, AKASHRAJ RAGA (Mathematical Statistician and Engineering Applications, 2022)
A wireless sensor network contains plenty of distributed sensor nodes mainly deployed to sense and deliver the collected information towards the destination node. sensor nodes are have limited resources like minimum memory, less computation capability, short range transmission and unreplaceble batteries, hence maintaining a reasonable network lifetime with better packet transmission rate for certain guarantee of Quality of Service is highly challenging. Currently, hierarchal routing schemes are widely used to face the design challenges to provide better efficiency for routing the packets and network lifetime enhancement using different routing approaches. However, hierarchical routing algorithms focus more on clustering of the nodes and routing for network lifetime and Quality of Service. In this work, author introduced different hierarchal routing algorithms with respect to quality of service. The proposed decision based routing scheme offers desired network performance followed by better results over existing state of routing protocol. Decision based routing algorithms computes the optimal path among the cluster heads which are used to transmit the data. This new routing approach consider the distance from the particular cluster head where data is originated to the base station, neighbor cluster head to base station, residual energy of current round. We compute the decision value of all the eligible cluster heads. The largest decision value node is selected as the next hop for packet transmission. The comparative results shows that the proposed decision based approach gives better performance in terms of packet delivery ratio, end to end delay, throughput and other QoS Parameter.